Fifteen-minute consultation: A structured approach to the management of chronic cough in a child. Issue 2 (5th August 2017) - Alviani, Cherry; Ruiz, Gary; Gupta, Atul
Abstract : Coughing is a primary pulmonary defence mechanism that enhances clearance of secretions and particles from the airways and protects against aspiration of foreign materials. Coughing may affect 30% of children at any given time (1). Many are healthy children but some may have serious underlying disease. Childhood cough accounts for a large number of consultations and 80% of families who are referred to a paediatric respiratory clinic for chronic cough have sought medical advice five times or more (2). The majority of childhood coughs are secondary to an acute respiratory tract infection and will improve once the infection resolves, usually within 1 to 3 weeks. With pre-school children who may experience between 6 and 10 respiratory infections a year differentiating acute recurrent cough from chronic cough is key (Table 1). Chronic cough can significantly impact a family's quality of life, as it affects the child's sleep, school attendance and play. Parents experience distress and anxiety, worrying that the cough may lead to long-term chest damage or even death (3). This article aims to guide clinicians through the assessment of the child with a chronic cough. It will discuss identifying causes, use of first line investigations, initiating appropriate management and addressing parental anxiety and exacerbating factors (4, 5).